Development of Gamification-Based Wayground Learning Media on Geographical Conditions Material in Junior High School - Ibrahim, Jodi Sadam; Fauziah, Vera Sophia (Edukasi IPS, 2025)
Geography instruction at the Junior High School (SMP) level often encounters obstacles regarding low student interest and comprehension due to material presentations that tend to be abstract and monotonous. This research aims to develop and test the effectiveness of "Wayground" gamification-based learning media in enhancing student interest and learning outcomes on the topic of Geographical Conditions and Interactions with Foreign Nations. The study employs the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) with a One-Group Pretest-Posttest experimental design. The research subjects consisted of 40 eighth-grade students at SMP Negeri 9 South Tangerang. The feasibility of the media was confirmed through expert validation (material and media experts), achieving a combined average score of 89.95%, categorized as "Very Feasible". Data analysis using a paired sample t-test indicated a significant improvement (Sig. 0.000) in student scores. The average score increased by 9.80 points, rising from 71.70 in the pretest to 81.50 in the posttest. These findings demonstrate that the use of Wayground media is effective in creating an interactive learning environment and tangibly increasing student interest and understanding of geography material.